Comparison of acute physiological and psychological responses between moderate-intensity continuous exercise and three regimes of high intensity interval training - Olney, N.; Wertz, T.; LaPorta, Z.; Mora, A.; Serbas, J.; Astorino, T. A. (The Journal of Strength and Conditioning Research, 2018)
High-intensity interval training (HIIT) elicits similar physiological adaptations as moderate-intensity continuous training (MICT) despite less time commitment. However, there is debate whether HIIT is more aversive than MICT. This study compared physiological and perceptual responses between MICT and 3 regimes of HIIT. Nineteen active adults (age = 24.0 ± 3.3 years) unfamiliar with HIIT initially performed ramp exercise to exhaustion to measure maximal oxygen uptake (VO2max) and determine workload for subsequent sessions, whose order was randomized. Sprint interval training (SIT) consisted of six 20-second bouts of "all-out" cycling at 140% of maximum watts (Wmax). Low-volume HIIT (HIITLV) and high-volume HIIT (HIITHV) consisted of eight 60-second bouts at 85% Wmax and six 2-minute bouts at 70% Wmax, respectively. Moderate-intensity continuous training consisted of 25 minutes at 40% Wmax. Across regimes, work was not matched. Heart rate (HR), VO2, blood lactate concentration (BLa), affect, and rating of perceived exertion (RPE) were assessed during exercise. Ten minutes postexercise, Physical Activity Enjoyment (PACES) was measured via a survey. Results revealed significantly higher (p = 0.05) VO2, HR, BLa, and RPE in SIT, HIITLV, and HIITHV vs. MICT. Despite a decline in affect during exercise (p < 0.01) and significantly lower affect (p = 0.05) during all HIIT regimes vs. MICT at 50, 75, and 100% of session duration, PACES was similar across regimes (p = 0.65), although it was higher in women (p = 0.03). Findings from healthy adults unaccustomed to interval training demonstrate that HIIT and SIT are perceived as enjoyable as MICT despite being more aversive.